Simulação de perdas de solo em função de cenários de adequação ambiental em microbacias agrícolas - De Barros Ferraz, Silvio Frosini; Pereira, Matheus Fernando [UNESP]; De Paula, Felipe Rosetti [UNESP]; Vettorazzi, Carlos Alberto; Alvares, Clayton Alcarde (My University, 2013)
In São Paulo state, deforestation and agriculture activities are increasing soil losses processes, especially in areas of susceptible soils where soil conservation practices are not adopted. Environmental adequacy at property level regarding Permanent Protection Areas and Legal Reserves is considered a potential factor for reducing soil losses and it was based on this fact that we assessed soil losses of different scenarios of environmental adequacy. Simulations of erosive processes were carried out in 15 catchments of the Corumbataí river basin, with different forest restoration scenarios, as well as the current situation of land use/ land cover. The scenarios include reforestation of Permanent Preservation Areas (PPA); the reforestation hydrological sensitive areas; and two scenarios, the Legal Reserve installation in 20% of each catchment, being one of them for most critical areas in terms of erosion and the other at random. It was observed that the establishment of PPA and the reforestation of hydrological sensitive areas (HSA), offered a small contribution to the control of the erosive process, resulting in a reduction of 10% and 7.4%, respectively, while the legal reserve in critical areas has the significant reduction of 69.8%. The random scenario, in turn, resulted in a reduction of 21.4% of erosion. Results show that reforestation can reduce soil losses, but previous studies of land prioritization and planning could significantly increase its efficiency.
Simulation of soil losses according to environmental adequacy law scenarios in agricultural catchments
Keywords: Erosion; Reforestation; Usle; Agricultural catchments; Conservation practices; Current situation; Forest restoration; Its efficiencies; Land use/ land covers; Prioritization; Agriculture; Catchments; Deforestation; Runoff; Soil conservation; Soils; Environmental regulations; Conservation; Regulations; Soil